2022
DOI: 10.1155/2022/7868248
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Household Livelihood Diversification: The Case of Kebri Dahar District, Korahey Zone of Somali Region, Ethiopia

Abstract: In Ethiopia, livelihood diversification has become a major source of income for rural communities. This study was carried out in rural kebeles in the Kebri Dahar district, and it focuses on livelihood diversification strategies and the factors that affect livelihood diversification. The collected types of data were from primary and secondary sources based on a qualitative and quantitative basis. Multistage sampling techniques were employed in selecting the representative households of 119 respondents. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Furthermore, a study conducted among peri-urban households in Amhara Regional State, Ethiopia, found that diversification of livelihoods was crucial to addressing poverty and food insecurity and improving the welfare of peri-urban people [13]. In the Kebri Dahar district of Ethiopia, livelihood diversification has positively impacted food security and should be promoted to enhance security in the area [14]. These studies demonstrate the potential of livelihood diversification strategies to improve the well-being of rural households and enhance their resilience in the face of environmental and economic challenges.…”
Section: Case Studies and Success Storiesmentioning
confidence: 99%
“…Furthermore, a study conducted among peri-urban households in Amhara Regional State, Ethiopia, found that diversification of livelihoods was crucial to addressing poverty and food insecurity and improving the welfare of peri-urban people [13]. In the Kebri Dahar district of Ethiopia, livelihood diversification has positively impacted food security and should be promoted to enhance security in the area [14]. These studies demonstrate the potential of livelihood diversification strategies to improve the well-being of rural households and enhance their resilience in the face of environmental and economic challenges.…”
Section: Case Studies and Success Storiesmentioning
confidence: 99%